PREOPERATIVE MANAGEMENT OF PATIENTS ON CHRONIC ANTITHROMBOTIC THERAPY WHO REQUIRE ELECTIVE NON-CARDIAC SURGERY: English - Živadinović, Jelena (Acta medicae Medianae, 2023)
Preoperative management of antithrombotic therapy (antiplatelet and anticoagulant therapy) is challenging since discontinuation of therapy carries a risk of the thromboembolic event and surgery carries a risk of bleeding. An optimal balance between thromboembolic and bleeding risk must be reached and the decision whether to stop antithrombotic therapy or not be made. Each patient requires an individual assessment. That means estimating bleeding and thromboembolic risk for each patient. Bleeding risk is based on patient-related risk factors and risk associated with the surgical procedure. Thromboembolic risk is more complex to calculate. If the decision is to stop antithrombotic therapy, the next question is how long before the surgery it should be stopped and whether the bridging therapy is required.